The "Uniate" Identity and the Construction of "Eastern Orthodoxy": Reflections on the Confessionalization Process in the Slavic East. - Avvakumov, Yury P. (Catholic Historical Review)
The article focuses on the origins of Eastern Catholic and Eastern Orthodox identities in the early modern and modern Slavic East. The concept of confessionalization can serve as a helpful tool in exploring questions of ecclesial identity. Applied to the Slavic East, the confessionalization paradigm helps to uncover both continuities and discontinuities in post-Byzantine religious history, approached in a comparative East-West perspective. The article critically engages with contemporary scholarship on the subject and seeks to contribute to a rethinking of some of the most common assumptions about the world of Eastern Christianity and the place of the Eastern Catholic churches in it. The approach of the article bridges history and ecclesiology.